1989
DOI: 10.1093/jac/23.6.915
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of catheter-associated Gram-negative bacilluria with norfloxacin by selective decontamination of the bowel and high urinary concentration

Abstract: Oral norfloxacin prevented Gram-negative bacilluria in female patients with hip fractures, who needed medium-term transurethral catheterization. This was shown in a placebo-controlled double-blind study of 34 patients. Seventeen of these received a suspension containing 200 mg norfloxacin and 500 mg amphotericin B, twice daily. In the placebo group, six cases of Gram-negative bacilluria had occurred by day 7, as compared with no cases during a median time of catheterization of 23 days in the group on medicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…21 In general, systemic antibiotic drug therapy tends to be most useful in patients requiring urinary catheterization for 3 to 14 days. 21,[68][69][70][71][72][73] Those catheterized for shorter durations are not at high enough risk *Number of patients who developed bacteriuria/total number of participants assigned to each group. †Odds of developing bacteriuria in the silver-coated catheter vs control catheter groups; CI indicates confidence interval.…”
Section: Systemic Antibiotic Drug Therapymentioning
confidence: 99%
“…21 In general, systemic antibiotic drug therapy tends to be most useful in patients requiring urinary catheterization for 3 to 14 days. 21,[68][69][70][71][72][73] Those catheterized for shorter durations are not at high enough risk *Number of patients who developed bacteriuria/total number of participants assigned to each group. †Odds of developing bacteriuria in the silver-coated catheter vs control catheter groups; CI indicates confidence interval.…”
Section: Systemic Antibiotic Drug Therapymentioning
confidence: 99%
“…Despite demonstrating a benefit in randomized control trials, especially in patients catheterized for three to 14 days [22,148,172,251,254,259], the use of systemic antibiotic prophylaxis for prevention of CAUTI is not routinely recommended [164,192]. Recovery of resistant organisms in the populations studied was inconsistent.…”
Section: Prophylactic Antibioticsmentioning
confidence: 99%
“…In the catheterised patient the prophylactic use of antibiotics reduces the incidence of bacteriuria initially and success has been reported using trimethoprim, sulphamethoxazole or nitrofurantoin; 62 ampicillin; 63 nor¯oxacin 64 and cipro¯oxacin. 65 Studies on the long term e cacy of prophylactic antibiotics have, however, shown no bene®t either in reducing the rate of bacteriuria, 66 or symptoms.…”
Section: Prophylactic Antibioticsmentioning
confidence: 99%